The entrepreneurial adventure : embracing risk, change, and uncertainty - James, Oliver; James, David (Entrepreneurship and small business management collection., 2020)
This book is perfect for anyone looking at business and entrepreneurship. It will be ideal for anyone with an interest in business and anyone who has aspirations to start their own business, outlining key principles of the entrepreneurial adventure and the business world, bringing it to life using case studies.This book contains useful and practical information about business and entrepreneurship and will aim to give a robust understanding of the theory and real-world implications of running a successful business. This book describes and explains the whole process from understanding the implications and risks, the start-up stage through to future expansion. The authors clearly demonstrate that if you follow the good business habits and practices that are described in this book consistently, you really can achieve entrepreneurial success and the opportunities that come with it.